Occurrence and Photo-Identification of Killer Whale in the Gulf of Tomini - Verrianto Madjowa; Abdul Hafidz Olii; Alfi Sahri Baruadi; Aziz Salam (Jambura Edu Biosfer Journal, 2024)
The study aims to report the occurrence and to present photo-identification of killer whales (Orcinus orca) in the Gulf of Tomini. This article is an attempt to provide basic data for further research on cetacean in Indonesia. The study was conducted from February 2017 to February 2019 in waters along the coast of Gorontalo Province in the Gulf of Tomini. Recorded videos and photos were collected, and interviews were conducted with fishers and tour guides. Observations were made at coastal waters near the villages where the occurrence of killer whales has been reported. Focus group discussions were held in a number of places in the study area by utilizing local traditional ecological knowledge. Data were analyzed in a descriptive-qualitative approach. The date of occurrence is sorted chronologically at each location. Photographs or videos were captured for photo-identification. The results showed that the occurrence of killer whales are almost evenly distributed throughout the year regardless of the monsoons. Killer whales usually appear in pods of up to five individuals, with a few exceptions of solo appearances. The resulting photo-identification displays four individuals from four different pods.